Murepavadin, a Small Molecule Host Defense Peptide Mimetic, Activates Mast Cells via MRGPRX2 and MrgprB2 - Amponnawarat, Aetas; Chompunud Na Ayudhya, Chalatip; Ali, Hydar (Frontiers in Immunology, 2021)
Pseudomonas aeruginosa is a frequent cause of hospital-acquired wound infection and is difficult to treat because it forms biofilms and displays antibiotic resistance. Previous studies in mice demonstrated that mast cells (MCs) not only contribute to P. aeruginosa eradication but also promote wound healing via an unknown mechanism. We recently reported that host defense peptides (HDPs) induce human MC degranulation via Mas-related G protein-coupled receptor-X2 (MRGPRX2). Small molecule HDP mimetics have distinct advantages over HDPs because they are inexpensive to synthesize and display high stability, bioavailability, and low toxicity. Murepavadin is a lipidated HDP mimetic, (also known as POL7080), which displays antibacterial activity against a broad panel of multi-drug-resistant P. aeruginosa. We found that murepavadin induces Ca2+ mobilization, degranulation, chemokine IL-8 and CCL3 production in a human MC line (LAD2 cells) endogenously expressing MRGPRX2. Murepavadin also caused degranulation in RBL-2H3 cells expressing MRGPRX2 but this response was significantly reduced in cells expressing missense variants within the receptor’s ligand binding (G165E) or G protein coupling (V282M) domains. Compound 48/80 induced β-arrestin recruitment and promoted receptor internalization, which resulted in substantial decrease in the subsequent responsiveness to the MRGPRX2 agonist. By contrast, murepavadin did not cause β-arrestin-mediated MRGPRX2 regulation. Murepavadin induced degranulation in mouse peritoneal MCs via MrgprB2 (ortholog of human MRGPRX2) and caused increased vascular permeability in wild-type mice but not in MrgprB2-/- mice. The data presented herein demonstrate that murepavadin activates human MCs via MRGPRX2 and murine MCs via MrgprB2 and that MRGPRX2 is resistant to β-arrestin-mediated receptor regulation. Thus, besides its direct activity against P. aeruginosa, murepavadin may contribute to bacterial clearance and promote wound healing by harnessing MC’s immunomodulatory property via the activation of MRGPRX2.